Use of Gallery Type Active Learning Strategies in Improving Social Studies Learning Outcomes in Junior High School Students - Allya Nurramadhan; Abdul Haris Fatgehipon; Sujarwo (Institute Journal and Publication Muhammadiyah University of Buton, 2024)
The role of the teacher in learning is also very important to help students understand and grasp the material that has been presented. Teachers need students who are active and have self-confidence in order to produce two-way learning. Implementing teacher-centered learning can lead to passive classroom conditions. Students tend to get bored with learning, and create unconducive classroom conditions. As a result, students cannot maximize their learning outcomes according to the criteria. Teachers as educators must use several methods to see the development of student learning outcomes and also increase student activity This study was carried out because it saw that the learning outcomes in social studies subjects of students were still low and had not reached the minimum criteria score. This research aims to improve the learning outcomes of students in grades VII-C at SMPN 163 Jakarta. This type of research is a class action research that is carried out in three cycles. The results showed that the use of the Gallery type active learning strategy could increase learning outcomes by 28% in cycle 1, 50% in cycle 2, and 83% in cycle 3.